EFEKTIVITAS TERAPI MUSIK UNTUK MENINGKATKAN KEMAMPUAN MENGENAL ANGGOTA TUBUH BAGI ANAK TUNAGRAHITA SEDANG DI KELAS II C1 SLB NEGERI 1 PADANG - Rio Wijaya (Universitas Negeri Padang, 2014)
Abstrack: This research is motivated from problems in one child in tunagrahita child medium. Child have difficulties in recognizing limbs of the upper body, such as: hair, eyes, nose, ears and mouthThis reserach used experimental approach with single subject and by using A-B-A design. And for analyzing the data, the researcher used visual analysis grafic. The subject of this reserach were the students of Tunagrahita. It can be seen that, the ability of the students couldn’t know their own top body in six time meetings baseline(A1) such as: hair, eyes, ears, nose and ,mouth. The percentage of this about 0% in intervension (B) for nine time meetings with the highest score 100%. While baseline (A2) for four time meetings, it appeared that the range score 80% until 100% . the small percentage overlap data describe the influence of intervension by using a song is better for the effectivity of music theraphy to improve the ability of Tunagrahita about physical body. Because the students are able to show and mention their own physical body. In short, music song theraphy is affective to improve the ability of Tunagrahita students X of SLB 1 Padang about physical body. It is suggested tha teachers are able to give the lesson through song thus the students are easy to know their own physical body well. Bassicly, music song theraphy is good concept of teaching through palying and learning. Kata kunci: Music Theraphy ; Kemampuan Mengenal Anggota Tubuh; Tunagrahita